Our wives under the sea - Armfield, Julia (Flatiron Books, 2022)
"Leah is changed. Months earlier, she left for a routine expedition, only this time her submarine sank to the sea floor. When she finally surfaces and returns home, her wife Miri knows that something is wrong. Barely eating and lost in her thoughts, Leah rotates between rooms in their apartment, running the taps morning and night. As Miri searches for answers, desperate to understand what happened below the water, she must face the possibility that the woman she loves is slipping from her grasp. By turns elegiac and furious, wry and heartbreaking, Our Wives Under the Sea is a genre-bending exploration of the depths of love and grief at the heart of a marriage"--